Pengukuran Daya Saing Kampung Wisata di Kota Bandung - Hidayat, Taufiq; Muhtar, Arisman (Tourism Scientific Journal, 2024)
The success of a tourist destination in the world market cannot be separated from the influence of its competitiveness. The competitiveness of tourist destinations is an area that attracts the attention of tourism researchers. Tourism competitiveness has tremendous consequences for the tourism industry and is therefore of great interest to practitioners and policy makers. The approach to the competitiveness of tourist destinations has so far focused on the image or attractiveness of tourist destinations concentrating on attributes that are considered to attract visitors, such as climate, scenery and accommodation. There are various indicators used to measure the competitiveness index of tourist destinations, including those from the World Travel and Tourism Council (WWTC), which include the Human Tourism Indicator, Price Competitiveness Indicator, Infrastructure Development Indicator, Environment Indicator, Technology Advancement Indicator, Human Resources Indicator, Openness Indicator, Social Development Indicators. In general, these indicators are relatively general and not local specific in exploring the conditions and circumstances of a tourist attraction, even though this aspect is directly related to the conditions of a destination/tourist attraction. The aim of this research is to assess destination performance using indicators in the aspects of attractions/tourism objects, infrastructure, access, and services/management. In this study, data came from 50 tourists (n=50). The analysis used is the Importance-Performance Analysis (IPA) Model to create a ranking of various attributes of Tourism Villages which concerns 4 aspects, namely tourist attractions, facilities (amenities), access/affordability (access), and services. additional (ancillary), by analyzing which attributes have a level of correspondence between the level of importance and the level of performance. Based on the results of the analysis, the main indicators that must be improved are additional services, and attractions are still felt to not meet respondents' expectations. The management of Braga Tourism Village needs to improve the quality of its services, especially related to information services and cleaning staff, while the quality of services which are considered to be good needs to be maintained in order to provide comfort for visitors. The results obtained from Importance Performance Analysis (IPA) will be used to determine the right strategy to improve the company's performance.